Research on open innovation strategy and its performance in Korea smart media industry: Focusing on user innovation strategy - Cheongho Na; Eungdo Kim; Junseok Hwang (International Telecommunications Society (ITS), 2014)
With the rapid development of ICT, smart society has been arrived. Smart devices also make user's role change and be powerful. In other words, user's power is stronger by smart devices in smart media industry and especially social environment like application market is catalyst for growth of user's role and power. On the other hand, it is hard for a firm to have all abilities and sources in this sudden change. Therefore, firms have to make their strategy considering user's role. For that reason, firms can use networks such as university, researcher, firm and user from the viewpoint of open innovation. I argue that users have some roles as one of the main agents in smart media industry affecting firm's strategy and performance.
Keywords: 330; Open innovation; smart media industry; strategy; performance; user's role